2015
DOI: 10.5216/ree.v17i4.31084
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que interferem no atributo longitudinalidade da atenção primária à saúde: revisão integrativa

Abstract: Objetivou-se avaliar as evidências disponíveis na literatura acerca dos fatores que interferem no atributo longitudinalidade da Atenção Primária à Saúde. Trata-se de uma revisão integrativa, desenvolvida em maio de 2014, nas bases de dados eletrônicas: LILACS, PubMed e Scopus. Utilizaram-se os descritores "atenção primária à saúde" and “continuidade da assistência ao paciente”. Totalizaram 16 artigos analisados na íntegra. Os dados foram organizados segundo os aspectos da atenção do atributo longitudinalidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
7
1
10
Order By: Relevance
“…This relationship is implicit due to the continuous monitoring performed over time, in the face of multiple episodes of illness, and the development of health promotion, characterized by responsibility on the part of the health professional, and patient confidence. (4) In contrast to this, although it was not observed in the present research, a study demonstrated that Table 3. Crude and adjusted Poisson regression to the independent variables that were associated with high PHC score in the health care of children and adolescents with HIV (n = 527) …”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…This relationship is implicit due to the continuous monitoring performed over time, in the face of multiple episodes of illness, and the development of health promotion, characterized by responsibility on the part of the health professional, and patient confidence. (4) In contrast to this, although it was not observed in the present research, a study demonstrated that Table 3. Crude and adjusted Poisson regression to the independent variables that were associated with high PHC score in the health care of children and adolescents with HIV (n = 527) …”
Section: Resultscontrasting
confidence: 91%
“…(3) From the PHC attributes, the present study focuses on longitudinality, which is conceptualized as the existence of a regular source of care, ability to identify the elective population that should be cared for by the service, in addition to establishing a bond between patients and professionals. (3,4) The PHC longitudinality assessment is necessary to qualify the health care. Thus, actions such as treatment, assessment of health needs, transference between services, reduction of hospitalizations, and patient satisfaction with the care provided, will contribute to health promotion and disease prevention, considering the relationship of longitudinality in the integration of structural and procedural improvements for the qualification of care.…”
Section: Introductionmentioning
confidence: 99%
“…As these factors characterize a safe, quality care that meets the real needs of this population, it is necessary to invest in human resources aiming at full coverage, continuing education, standardization, and implementation of health care actions for the elderly. Furthermore, the results obtained in this study are in line with the literature regarding the organization of services, accessibility, and fragility of therapeutic bond relationships between users and health professionals as factors that may influence the longitudinality and safety of care (4,14) . In fact, the biological demand is what pushes users to seek the health care service, but the patients seek not only the resolution of the case but also expect the establishment of a relation of embracement and access to services (15) .…”
Section: Discussionsupporting
confidence: 88%
“…One of the main characteristics in PHC is the longitudinality in the care to the individual, encompassing actions promotion, protection and recovery of health, in a comprehensive and continuous way. The positive results intrinsically related to this service derive from the most appropriate diagnosis and treatment, reducing unnecessary referrals to other sectors of the network and the use of more complex procedures (19) .…”
Section: Discussionmentioning
confidence: 99%